Tantangan Multikulturalisme di Indonesia: Menyoal Relasi Agama dan Ruang Publik - Ayunda, Aretsa Zana; Urbaningkrum, Santi Mahmuda; Nusaibah, Afaf Wafiqoh; Septiana, Widya; Widyani, Saesari Salekhah Nur; H, Arief Rahman (Lembaga Yasin AlSys, 2022)
In people's lives a difference in religion, socializing, customs, and habits in carrying out daily activities will always exist. These differences are called diversity. However, not all diversity can be accepted by the whole community, there are also conflicts that arise as a result of these differences. The role of multiculturalism is needed to deal with the problems of differences that exist at this time. The purpose of this journal is to find out what are the challenges of multiculturalism that occur in society on religious and public issues by using library studies or library research as a research method. Many of the multicultural challenges that occur, especially in Indonesia, are related to religious relations and public space. In the challenges in the field of religion, there are many people who are not able to accept the existing differences so that conflicts regarding their respective religions continue to occur. Many people who are religious fanatics take advantage of this situation to divide the unity of Indonesian society for personal or group interests who do not agree with the existence of religious diversity. In addition, the existence of social media, which should be an ease in spreading news or information, is widely misused to spread information that is not yet clear, so that it becomes a big influence for people who read or hear the information.